2021
DOI: 10.13052/jcsm2245-1439.941
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Detection of HTTP Injection Attacks using Convolutional Neural Network and Deep Neural Network

Abstract: HTTP injection attacks are well known cyber security threats with fatal consequences. These attacks initiated by malicious entities (either human or computer) send dangerous or unsafe malicious contents into the parameters of HTTP requests. Combatting injection attacks demands for the development of Web Intrusion Detection Systems (WIDS). Common WIDS follow a rule-based approach or a signature-based approach which have the common problem of high false-positive rate (wrongly classifying malicious HTTP requests)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…The authors achieved a detection rate of 84.13% in model tests performed on the ECML-PKDD dataset. In another similar web anomaly study [11], the authors showed that the classification performances are increased by using the word embedding method in single deep learning models based on CNN and DNN. However, the weighted average of detection rates for attack types in tests performed on ECML-PKDD is calculated as 84.0% [11].…”
Section: Related Workmentioning
confidence: 99%
See 4 more Smart Citations
“…The authors achieved a detection rate of 84.13% in model tests performed on the ECML-PKDD dataset. In another similar web anomaly study [11], the authors showed that the classification performances are increased by using the word embedding method in single deep learning models based on CNN and DNN. However, the weighted average of detection rates for attack types in tests performed on ECML-PKDD is calculated as 84.0% [11].…”
Section: Related Workmentioning
confidence: 99%
“…In another similar web anomaly study [11], the authors showed that the classification performances are increased by using the word embedding method in single deep learning models based on CNN and DNN. However, the weighted average of detection rates for attack types in tests performed on ECML-PKDD is calculated as 84.0% [11]. This demonstrates that a single model cannot achieve sufficient success in classifying web attack types.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations